2008
DOI: 10.1109/tits.2008.928259
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Real-Time Roadside CO and $\hbox{NO}_{2}$ Concentrations Using Neural Networks

Abstract: Abstract-The main aim of this paper is to develop a model based on neural network (NN) theory to estimate real-time roadside CO and NO 2 concentrations using traffic and meteorological condition data. The location of the study site is at a road intersection in Melton Mowbray, which is a town in Leicestershire, U.K. Several NNs, which can be classified into three types, namely, the multilayer perceptron, the radial basis function, and the modular network, were developed to model the nonlinear relationships that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
(9 reference statements)
0
19
0
Order By: Relevance
“…Morning and afternoon periods are regarded as peak traffic periods while midday is identified as the offpeak period. The actual pollution level varies remarkably at fine-time scales around intersections (Zito et al, 2008), and thus PM 2.5 (mg/m 3 ) and CO (ppm (parts per million)) were measured at minute level in this study. Two sets of portable monitors were used to detect both pollutants at roadside and setbacks.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morning and afternoon periods are regarded as peak traffic periods while midday is identified as the offpeak period. The actual pollution level varies remarkably at fine-time scales around intersections (Zito et al, 2008), and thus PM 2.5 (mg/m 3 ) and CO (ppm (parts per million)) were measured at minute level in this study. Two sets of portable monitors were used to detect both pollutants at roadside and setbacks.…”
Section: Data Collectionmentioning
confidence: 99%
“…Consequently, there are still some challenges to reach agreements on how these correlated factors affect street-scale pollutant variation in a statistical sense. Moreover, as the traffic-related emission intensity and local meteorology are variable, air pollutants around an intersection can significantly vary at minute scale (Zito et al, 2008;Galatioto and Zito, 2009;Soulhac et al, 2009;Tiwary et al, 2011;He and Lu, 2012). Studies further found that short-term exposures (e.g., minutes) to high pollutant levels are even more serious compared to long-term general exposures (e.g., annual, monthly, daily) (Brook et al, 2002;Grivas and Chaloulakou, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Different neural network topologies are also considered. The performance of three different neural network topologies (MLP, RBF and Modular-ANN) for predicting roadside concentrations of CO and N O 2 in Melton Mowbray, UK, are compared in [19]. The transferability of these models is then considered by applying them to data from another site in Leicester, UK, concluding that whilst performance is degraded, it is still able to provide a useful prediction capability.…”
Section: Air Quality Forecastingmentioning
confidence: 99%
“…Prediction of real-time roadside CO and NO 2 concentrations using multilayer perceptrons, modular and RBF networks is the subject of [8]. All networks are trained on traffic and meteorological data available for a road junction in the UK, then tested on another intersection with similar traffic patterns and weather.…”
Section: Offboard Applicationsmentioning
confidence: 99%